2013
DOI: 10.1074/jbc.m112.417717
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglutamate and O-Linked Glycan Determine Functional Production of Anti-IL17A and Anti-IL22 Peptide-Antibody Bispecific Genetic Fusions

Abstract: Background: Protein biosynthesis and secretion are essential biological processes for therapeutic protein production. Results: Generating functional anti-IL17A and anti-IL22 peptide-antibody bispecific therapeutic proteins requires pyroglutamate addition and O-linked glycan removal. Conclusion: Post-translational modifications play critical roles in determining structure and function of therapeutic proteins. Significance: The peptide-antibody genetic fusion is promising for targeting multiple antigens in a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The loss of cellular activity of 31 was most likely due to the degradation of the N-terminus of 31 , since peptide 31 was shown to be able to bind to IL-17A with similar affinity as HAP itself 27 . Furthermore, our previous work had reported that in antibody fusions the uncapped peptide was degraded under cell assay conditions with removal of the first 1-3 residues to inactive products with the same N-terminal sequences as peptides 32 – 34 27 . In this work, 32 – 34 are capped by protective acetyl group and reflect the same inactivity as reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of cellular activity of 31 was most likely due to the degradation of the N-terminus of 31 , since peptide 31 was shown to be able to bind to IL-17A with similar affinity as HAP itself 27 . Furthermore, our previous work had reported that in antibody fusions the uncapped peptide was degraded under cell assay conditions with removal of the first 1-3 residues to inactive products with the same N-terminal sequences as peptides 32 – 34 27 . In this work, 32 – 34 are capped by protective acetyl group and reflect the same inactivity as reported.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial approach was to identify peptide inhibitors which could serve as leads for the development of anti-inflammatory therapeutics that could be used alone or in combination with other agents. Our efforts resulted in discovery of a high affinity IL-17A peptide antagonist (HAP), which we attempted to increase the functional production and pharmacokinetics after fusing HAP to antibodies for evaluation as a bispecific therapeutic in animal studies 27 28 . Unfortunately, this past work revealed stability issues of the uncapped HAP in cell culture Here, we provide the details of the discovery and optimization that led to HAP and report the complex structure of IL-17A with HAP, which provides structure based rationalization of peptide optimization and structure activity relationship (SAR).…”
mentioning
confidence: 99%
“…One of the adverse effects of O-linked glycans on therapeutic proteins is heterogeneity [15, 107]. Recently O-linked glycans are found inhibiting the binding activity and efficacy of a therapeutic peptide-antibody bispecific fusion by blocking its interaction with cytokine IL17A [53]. …”
Section: Golgi Modificationsmentioning
confidence: 99%
“…Pyroglutamate formation is found resistant to amino peptidases and therefore is proposed as a stabilization mechanism [169]. It has been recently demonstrated that engineering an N-terminal pyroglutamate to a peptide-antibody bispecific genetic fusion molecule can restore its IL17A neutralizing activity in a cell-based assay by preventing N-terminal degradation [53]. …”
Section: Exocellular Modificationsmentioning
confidence: 99%
See 1 more Smart Citation